Techno‐functional and nutritional properties of full‐bran and low‐bran canaryseed flour, and the effect of solvent‐de‐oiling on the proteins of low‐bran flour and isolates. Issue 4 (21st February 2022) - Perera, Suneru P.; Konieczny, Dellaney; Ding, Ke; Hucl, Pierre; L'Hocine, Lamia; Nickerson, Michael T.
Abstract: Background and Objectives: The differences in functional and nutritional properties of whole and white canaryseed flour obtained by roller milling was investigated in this study. Moreover, the effect of solventde‐oiling on the structural, functional, and nutritional properties of the canaryseed protein present in the white flour and derived protein‐isolates was also studied. Findings: There was no significant difference between the protein content of whole (21.3%) and white (21.4%) canaryseed flours whereas, oil, ash, total starch, non‐starch carbohydrates, phytic acid, and total phenolic contents showed significant differences between whole and white canaryseed flours. Water and oil holding capacity and emulsifying capacity of whole seed flour were better than that of white flour whereas, emulsion and foaming stability, and foaming capacity were similar. The IVPDCAAS of white flour was 23%, was significantly lower than that of the whole seed flour (31.2%). Ethanol had a higher efficiency for canaryseed oil and phospholipid extraction than hexane. Linolenic acid and phosphatidylcholine were, respectively, the major fatty acid and phospholipid extracted by both ethanol and hexane. None of these solvents caused protein denaturation and showed a positive impact on certain functionalities. Canaryseed protein was found to be thermally stable, with a peak denaturation temperature of 108°C. Conclusions: Whole canaryseed flour showed better functionality and nutrition than white flour. The white flour, however, was found to be a more favorable starting material for protein fractionation. Solvent de‐oiling did not have a negative impact on canaryseed protein, which exhibited a high thermal stability. Significance and Novelty: This study provides information on functional and nutritional properties of different value‐added protein products of canaryseed and on the effect of solvent de‐oiling on the protein quality. Such understanding is beneficial for the protein ingredient industry.